State Terrorism and Human Rights : International Responses since the End of the Cold War. - Duncan, Gillian (Cass series on political violence., 2013)
This book aims to improve understanding of the broad trends in the utilisation of political violence by examining the use of state terror in world politics. The ending of the Cold War and the overthrow of communism in Eastern Europe led many to assume that this presaged the demise of the one-party terror regime and acceptance of Western concepts of democracy, freedom and human rights throughout the international system. But of course this did not end state terror. The totalitarian one-party state still exists in North Korea and China, and there are numerous military regimes and other.